2017
DOI: 10.1097/md.0000000000007382
|View full text |Cite
|
Sign up to set email alerts
|

Femoral nerve block versus fascia iliaca block for pain control in total knee and hip arthroplasty

Abstract: Background:This meta-analysis aimed to perform a meta-analysis to compare the efficiency and safety between femoral nerve block (FNB) and fascia iliaca block (FIB) for postoperative pain control in patients undergoing total knee and hip arthroplasties.Methods:A systematic search was performed in Medline (1966-2017.05), PubMed (1966-2017.05), Embase (1980-2017.05), ScienceDirect (1985-2017.05) and the Cochrane Library. Inclusion criteria (1) Participants: Only published articles enrolling adult participants tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 26 publications
2
42
1
1
Order By: Relevance
“…Their study results also showed that FINB had lower opioid requirements than IVA. Another meta-analysis by Wang et al [38] included four studies and showed that FNB and FINB resulted in similar opioid requirements until 48 h postoperatively in patients undergoing total knee and hip arthroplasties. Taken together, we suggest the need for more studies to elucidate the impact of FNB on postoperative opioid requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Their study results also showed that FINB had lower opioid requirements than IVA. Another meta-analysis by Wang et al [38] included four studies and showed that FNB and FINB resulted in similar opioid requirements until 48 h postoperatively in patients undergoing total knee and hip arthroplasties. Taken together, we suggest the need for more studies to elucidate the impact of FNB on postoperative opioid requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound guidance is a superior technique for nerve block administration and may facilitate equivalent analgesic effect in FNB and FICB. It has been advocated that FICB is easier to perform with a better safety profile than FNB, therefore, utilising ultrasound‐guided FICB may improve the delays in analgesia. Using ultrasound guidance achieved a high success rate in both FNB and FICB administered with the vast majority of participants experiencing pain reduction post‐block.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to FNB, the risk of injury to the femoral nerve and femoral vessels is lessened when performing FICB. As a result of the safety profile and relative ease of administration, there is a growing preference for the use of FICB in EDs …”
Section: Introductionmentioning
confidence: 99%
“…Although they did find greater ambulation distances with lumbar plexus catheters, unlike Marino et al ,400 they could not detect intergroup differences in terms of pain, breakthrough analgesic consumption, and patient satisfaction 401. In a recent meta-analysis (five trials; 308 patients), Wang et al 402 set out to compare fascia iliaca and femoral blocks for THA: these authors concluded that fascia iliaca and femoral blocks result in equivalent analgesia. However, their findings should be interpreted wit caution, as all pooled trials have employed the conventional infrainguinal technique for fascia iliaca blocks.…”
Section: Controversial Areas Related To Outcomesmentioning
confidence: 96%